Optical imaging of interaural time difference representation in rat auditory cortex - Tsytsarev, Vassiliy; Fukuyama, Hidenao; Pope, Daniel L.; Pumbo, Elena; Kimura, Minoru (Frontiers in Neuroengineering, 2009)
We used in vivo voltage-sensitive dye (VSD) optical imaging to examine the cortical representation of interaural time difference (ITD), which is believed to be involved in sound source localization. We found that acoustic stimuli with dissimilar interaural time differences activate various localized domains in the auditory cortex. The main loci of the activation pattern shift up to 1 mm during the first 40 ms of the response period. We suppose that some of the neurons in each pool are sensitive to the definite interaural time difference and involved in the transduction of information about sound source localization, based on the interaural time difference. This assumption gives a reasonable fit to the Jeffress model in which the neural network calculates the ITD to define the direction of the sound source. Such calculation forms the basis for the cortex's ability to detect the azimuth of the sound source.